Digital transformation:|The influence of critical success factors on the modern working environment - Gün, Övül Elest. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Digital transformation became a worldwide known terminology as a result of rising importance and constant improvement of digital technologies, leading to higher attention of researchers and business professionals. Various aspects of digital transformation are observed and analyzed such as cause and effect, the way of its appearance or its meaning for the economy. Organizational perspective of digital transformation is analyzed in this study, together with its relevance for business and human capital. Main objective of this study is to assess the critical success factors of digital transformation, and observe their effect leading to a shift on business and human capital in the organizations, as well as with the organizational growth performance. The observation of the effects of business process practices and intrapreneurship towards digital transformation has not yet been done in detail. Therefore, a new theoretical framework is constructed based on related literature review and qualitative interviews. The framework is validated by using collected quantitative data from working professionals. Constructed hypotheses for seven constructs are analyzed using structural equation modelling. Results of the study show that innovation activities and digital transformation driven strategy are positively related to the change on business process practices and the intrapreneurship initiation. It is also concluded that organizational growth is positively affected by changes on business process practices.
Keywords: Technological innovations -- Social aspects.; Information technology -- Management.; Digital electronics -- Social aspects.